2017
DOI: 10.3389/fmicb.2017.00276
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis, Toll-like, RIG-I-like and NOD-like Receptors Are Pathways Jointly Induced by Diverse Respiratory Bacterial and Viral Pathogens

Abstract: Lower respiratory tract infections are among the top five leading causes of human death. Fighting these infections is therefore a world health priority. Searching for induced alterations in host gene expression shared by several relevant respiratory pathogens represents an alternative to identify new targets for wide-range host-oriented therapeutics. With this aim, alveolar macrophages were independently infected with three unrelated bacterial (Streptococcus pneumoniae, Klebsiella pneumoniae, and Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 93 publications
1
17
0
1
Order By: Relevance
“…Infection with PR8 increased the recruitment of RIG-I to the mitochondria as compared to uninfected control cells (MOCK). This association was higher in cells infected with delNS1 than in cells infected with the PR8 virus, in agreement with the increased antiviral response observed in delNS1 infected cells [39,40]. The recruitment of RIG-I to mitochondrial fractions was not modified by Dot1L inhibition in delNS1 infection.…”
Section: Ns1 Protein Modulates the Dot1l Control Of Rig-i-mavs Associsupporting
confidence: 83%
See 1 more Smart Citation
“…Infection with PR8 increased the recruitment of RIG-I to the mitochondria as compared to uninfected control cells (MOCK). This association was higher in cells infected with delNS1 than in cells infected with the PR8 virus, in agreement with the increased antiviral response observed in delNS1 infected cells [39,40]. The recruitment of RIG-I to mitochondrial fractions was not modified by Dot1L inhibition in delNS1 infection.…”
Section: Ns1 Protein Modulates the Dot1l Control Of Rig-i-mavs Associsupporting
confidence: 83%
“…The RNA analysis of genes involved in the interferon signaling pathway indicated that influenza virus infection stimulates TRIM25 expression, which in turn markedly decreases when infected human alveolar epithelial cells are treated with a Dot1L inhibitor (Table 1, Figure 6). Characterization of the immune response induced by different pathogens in murine alveolar macrophages infected at high MOI [40], showed a higher induction of TRIM25 expression in delNS1 infected cells compared with PR8 infection (data not shown). TRIM25-mediated ubiquitination stimulates RIG-I tetramerization, allowing RIG-I-MAVS interaction, which triggers the induction of the innate immune response [45][46][47].…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptomic and proteomic studies have shown the profound impact of HRSV on the physiology of respiratory epithelial cells, its main targets for infection. However, most of those studies have focused on the early innate immune response elicited in the infected cells [12][13][14]. Although, changes in other aspects of the virus-host cell interactions have also been reported, including those involving cell growth, cytoskeleton organization and mitochondrial electron transport [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that RIG‐I is a critical immune receptor in infection with the bacterium that possesses immunostimulatory lipopolysaccharide in the early stage 22 . The IFN response is the primary defense system by viral pathogens 23 .…”
Section: Discussionmentioning
confidence: 99%